Enhancing Norway’s Local Emergency Preparedness with Municipal Crisis Team Exercising - Andreassen, Natalia; Elvegård, Rune; Eid, Jarle; Espevik, Roar (Proceedings of the International ISCRAM Conference, 2025)
This case study describes and discusses the outcomes of an emergency preparedness exercise designed to enhance team processes in a municipal crisis response team. The study presents the case of an emergency preparedness exercise simulating a cruise ship in distress in the High North. The exercise was facilitated by a cross-disciplinary team of faculty members and subject matter experts from emergency preparedness organizations. The results highlight the student assessment of the exercise and identify critical exercise design factors associated with enhanced learning, such as scenario realism, timely preparation, and regular practice. The core members of crisis response teams in municipalities invest limited time and resources in team training; thus, it is essential that their training is effective and grounded in relevant risk and vulnerability analyses and evidence-based problems in municipalities. The study recommends the development of competencies in local emergency response teams based on theoretical frameworks of experiential team learning and shared mental model research.